Complex Assessment of the Functional State of the Urinary System in Preclinical Studies. Part 2. Markers of Nephrotoxicity (Review) - M. V. Miroshnikov; K. T. Sultanova; M. N. Makarova; N. M. Faustova; S. O. Khan; E. A. Loseva (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. The determination of nephrotoxicity markers is a useful and necessary step in the detection of renal injury in animal experiments; these markers help accurately localise organ damage. With multiple damaging agents, known nephrotoxicity mechanisms, and laboratory animal species, there is currently no widely accepted renal injury marker that meets all the prerequisites.AIM. This study aimed to collate literature data on nephrotoxicity markers, evaluate their prognostic significance, and formulate general recommendations for assessing urinary system function in preclinical studies.DISCUSSION. This article describes a comparative analysis of the nephrotoxicity markers recommended by regulatory authorities for monitoring drug-induced kidney injury. According to the results, the most commonly used and prognostically significant markers of acute kidney injury in preclinical studies are cystatin C, albumin, total protein, kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin-2 (NGAL), and clusterin. Chronic kidney injury markers include the above, plus the glomerular filtration rate, creatinine, urea, and osteopontin. An electrolyte panel can be used for the differential diagnosis of pre-renal azotaemia and acute kidney injury. Potential limitations for the routine use of kidney injury markers in preclinical research include the high cost of their quantitative determination and the lack of information on the applicability of data obtained from different species of laboratory animals.CONCLUSIONS. Having compared the prognostic significance of common biomarkers, the authors provided general recommendations for a comprehensive preclinical assessment of urinary system function, including laboratory investigations, instrument-based tests, and necropsy. A preclinical study design should be based on the study aims, the species and number of animals used, and special considerations for the test article.